Integration of decoy domains derived from protein targets of pathogen effectors into plant immune receptors is widespread. Issue 2 (5th February 2016) - Kroj, Thomas; Chanclud, Emilie; Michel‐Romiti, Corinne; Grand, Xavier; Morel, Jean‐Benoit
Summary: Plant immune receptors of the class of nucleotide‐binding and leucine‐rich repeat domain (NLR) proteins can contain additional domains besides canonical NB‐ARC (nucleotide‐binding adaptor shared by APAF‐1, R proteins, and CED‐4 (NB‐ARC)) and leucine‐rich repeat (LRR) domains. Recent research suggests that these additional domains act as integrated decoys recognizing effectors from pathogens. Proteins homologous to integrated decoys are suspected to be effector targets and involved in disease or resistance. Here, we scrutinized 31 entire plant genomes to identify putative integrated decoy domains in NLR proteins using the Interpro search. The involvement of the Zinc Finger–BED type (ZBED) protein containing a putative decoy domain, called BED, in rice ( Oryza sativa ) resistance was investigated by evaluating susceptibility to the blast fungus Magnaporthe oryzae in rice over‐expression and knock‐out mutants. This analysis showed that all plants tested had integrated various atypical protein domains into their NLR proteins (on average 3.5% of all NLR proteins). We also demonstrated that modifying the expression of the ZBED gene modified disease susceptibility. This study suggests that integration of decoy domains in NLR immune receptors is widespread and frequent in plants. The integrated decoy model is therefore a powerful concept to identify new proteins involved in disease resistance. Further in‐depth examination of additional domains in NLR proteins promises to unravel many new proteins of the plant immune system. Abstract : See also the Commentary on this article by Malik & Van der Hoorn, 210 : 371–373.